The meaning of assuming dependency at home of a person with cardiovascular surgery : The vision of informal caregivers (2017)
ABSTRACT: Objective. Herein, the study sought to understand the significance for informal caregivers of assuming the dependency at home of an individual subjected to cardiovascular surgery. Methods. This was a phenomenological interpretative study conducted with eight adult participants, home caregivers of individuals with cardiovascular surgery discharged from intensive care units to their homes. An indepth interview was used as technique to collect the information and the procedures proposed by Cohen, Kahn, and Steeves were used for analysis. Results. Caregivers of individuals with cardiovascular surgery at home face situations that lead them to taking on the dependency of the person being cared. The significance participants granted to the experience was the lack of preparation to deal with it due to the unexpected way it emerged. This created a difficult situation, where feelings surfaced, like misgivings, fear, and stress during the time dedicated to caring. In some cases, the caregiver prolonged the dependency of caring for another. Conclusion. Undertaking the dependency of a person at home meant to caregivers coping with new situations without preparation. This dependency stirs feelings and sometimes limits participation by the person in their own care.